Negotiating the Transatlantic deal: the case of domestic constraints - Alina Petronela Alexoaei; Valentin Cojanu (Romanian Journal of European Affairs)
Progress towards a final agreement between the European Union and the US for the Transatlantic Trade and Investment Partnership (TTIP) stalled indefinitely in 2016. The negotiation process has been influenced by a wide and complex set of factors stemming from interdependent factors (mainly geopolitical), dependent factors that originate in global economic integration, and independent factors coming from domestic socio-economic, political and institutional constraints. Assuming the influential role of internal pressures and domestic political events, we single out in this paper the question of domestic politics whose specific contribution to the outcome of trade negotiations have been emphasized to a great extent by various studies. The paper pursues a three-pronged approach in order to: (1) identify the set of domestic constraints on both parties, (2) assess their influence on each’ side strategic position, and (3) suggest both available and desirable future courses of action to improve the negotiation outcome.